The central role of symptom severity and associated characteristics for functional impairment in misophonia - Möllmann, Anne; Heinrichs, Nina; Illies, Lisa; Potthast, Nadine; Kley, Hanna (Frontiers in Psychiatry, 2023)
Misophonia is characterized by a preoccupation with and strong emotional and behavioral reactions to certain triggers, mostly sounds related to eating and breathing. We applied functional impairment due to misophonic symptoms as a central criterion to investigate differences between clinical misophonia and normative decreased sound tolerance in a large non-random sample of n = 1.881 individuals from an online survey. We assessed the frequency of self-reported misophonia symptoms across various symptom measures, compared severity, triggers and emotional reactions, general psychopathology, interpersonal emotion regulation, and quality of life between both groups with and without functional impairing misophonia. Individuals with functional impairment due to misophonia (n = 839) revealed significantly higher general psychopathology symptoms, lower interpersonal emotion regulation skills, and lower quality of life than individuals without impairment (n = 1.042). Anxious/distressed and annoyed reactions to triggers were experienced more frequently compared to emotional reactions of disgust and sadness or depression in both groups. Overall, the group differences were primarily quantitative in nature. We discuss practical implications regarding classification and treatment and provide cutoffs for each symptom measure derived from group assignment for functional impairment.